Climate risk and precautionary cash holdings: Evidence from Chinese listed companies - Zhang, Wei; Yang, Kaidi; Li, Yulei (Frontiers in Environmental Science, 2023)
Using Chinese listed companies as the research setting, this study investigates the impact of climate risk on corporate precautionary cash holdings and further explores possible underlying channels. We first apply the text mining technique to construct the climate risk indicator. The regression results then show that climate risk has a significant and positive impact on corporate precautionary cash holdings. Such positive relationship is stronger for firms with small size and those located in central and eastern China. Further mechanism analysis indicates that risk taking and external financing play a mediating effect between climate risk and corporate precautionary cash holdings. Our findings have important practical implications for companies to make sustainability strategies against potential climate risks.